Aerobic and anaerobic poise of white swimming muscles of the deep-diving scalloped hammerhead shark: comparison to sympatric coastal and deep-water species - Royer, Mark; Garcia, Danielle; Dickson, Kathryn; Weng, Kevin C.; Meyer, Carl; Holland, Kim N.; Drazen, Jeffrey C. (Frontiers in Marine Science, 2024)
Scalloped hammerhead sharks (Sphyrna lewini) routinely perform rapid dives to forage on mesopelagic prey. These deep dives consist of intensive swimming followed by recovery periods in the surface mixed layer. Swimming muscle temperature profiles suggest that S. lewini suppresses gill function as a means to reduce convective heat loss during dives into cool water. Such intensive swimming behavior coupled with reduced respiration prompted us to test whether the aerobic and anaerobic metabolic capacities of the white swimming muscle tissue of this species are greater than those of other shark species from the same region. The activities of key enzymes used in aerobic and anaerobic metabolism provide an indirect indicator of the metabolic potential (“poise”) of a tissue. Here we measured the maximal activities [international units (µmol substrate converted to product per min, U) per gram of wet tissue mass at 10°C] of the citric acid cycle enzymes citrate synthase (CS) and malate dehydrogenase (MDH) and glycolytic enzymes pyruvate kinase (PK) and lactate dehydrogenase (LDH) from white swimming muscle of S. lewini. Enzyme activities, and ratios of these enzyme activities that indicate relative indexes of aerobic to anaerobic capacity, were compared to those measured in three sympatric coastal carcharhinid sharks and two deep-dwelling species, Echinorhinus cookei and Hexanchus griseus. This is the first report of swimming-muscle enzyme activity for these deep-dwelling species. In comparison to the other species, S. lewini had significantly higher activities of both LDH and MDH in the white muscle, and a higher MDH/CS ratio. The high LDH activities suggest that the white muscle of S. lewini relies on relatively high rates of anaerobic ATP production, with would result in build up of high lactate levels, during deep foraging dives. High MDH activity in S. lewini white muscle suggests the potential for lactate levels to be rapidly reduced when aerobic conditions are restored while in the surface mixed layer between dives. These biochemical characteristics may enable S. lewini to swim rapidly while suppressing gill function during deep dives and thereby exploit a very different ecological niche from sympatric shark species (e.g., coastal carcharhinids) and hunt more rapidly via faster swimming for deep-water prey compared to species that permanently inhabit deep depths.